Radip light-induced phosphorylation changes in microtubule related proteins in arabidopsis - Arico, Denise Soledad (2023)
Rapid hypocotyl elongation allows buried seedlings to reach the surface, where light triggers de-etiolation and inhibits hypocotyl growth mainly by phytochromes A, B and cryptochromes 1, 2. Dynamic phosphorylation/dephosphorylation events provide a mechanism to rapidly transduce light signals. Only recently we have begun to uncover the earliest phospho-signaling responders to light.Here, we report a large-scale phosphoproteomic analysis and identify 20 proteins that change their phosphorylation pattern after 20 min of white light pulse compared to darkness. Microtubule-associated proteins (MAPs) were highly overrepresented in this group. Among them, we studied CIP7 (COP1-INTERACTING-PROTEIN-7), which presented microtubule (MT) localization, in contrast to what was previously described. Phosphorylated isoform in Serine 915 (Sp915) of CIP7 was detected in etiolated seedlings but undetectable after a light pulse in the presence of photoreceptors, while its expression decays with long light exposure.